2012
DOI: 10.1155/2012/620967
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Stem Cell Transplantation for aBCR-FGFR1Myeloproliferative Neoplasm Presenting as Acute Lymphoblastic Leukemia

Abstract: Hematopoietic myeloproliferative neoplasms (MPNS) with rearrangements of the receptor tyrosine kinase FGFR1 gene, located on chromosome 8p11, are uncommon and associated with diverse presentations such as atypical chronic myeloid leukemia, acute myeloid leukemia, or an acute T- or B-lymphoblastic leukemia, reflecting the hematopoietic stem cell origin of the disease. A review of MPN patients with the t(8;22) translocation that results in a chimeric BCR-FGFR1 fusion gene reveals that this disease either present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Allogeneic hematopoietic stem cell transplantation (HSCT) is recommended for these patients. 2,5,7,8 …”
mentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation (HSCT) is recommended for these patients. 2,5,7,8 …”
mentioning
confidence: 99%
“…We describe the fourthknown case of B-ALL associated with the t(8;22)(p11.2q11.2) [1][2][3]. In addition, this B-ALL has associated cytogenetic anomalies not yet described in the literature; a del(11)(q13q23), an add(9)(p22), and a monosomy 7 were also present.…”
Section: Introductionmentioning
confidence: 77%
“…Recently, certain studies have reported that patients with t(8;22) exhibit similar morphological and clinical features to those observed in CML patients (2)(3)(4). Since the first case reported by Fioretos in 2001 (5), to the best of our knowledge, t(8;22)(p11;q11) has been reported in only 17 cases with hematological malignancies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Of these, 6 cases presented with atypical CML (2-4,6,7), 3 with myeloproliferative neoplasms (5,8,9), 3 with B-cell acute lymphoblastic leukemia (10-12) and 5 with other types of hematological neoplasms (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 81%